Association between DPM1 gene single nucleotide polymorphism and Henoch-Schönlein purpura in children - GAO Xin, ZHANG Qiuye, CHANG Hong, BAI Cui, WANG Dahai, SHAO Leping, LIN Yi (精准医学杂志)
Objective To investigate the association between DPM1 gene single nucleotide polymorphism and Henoch-Schönlein purpura in children. Methods A total of 156 children with Henoch-Schönlein purpura who were diagnosed and treated in The Affiliated Hospital of Qingdao University from April 2021 to March 2022 were enrolled as case group, and 152 healthy children who underwent physical examination during the same period of time were enrolled as control group. According to the presence or absence of the symptoms of abdominal pain and joint pain, the children were divided into abdominal pain group, non-abdominal pain group, joint pain group, and non-joint pain group; according to whether a child was comorbid with purpura nephritis, they were divided into purpura nephritis group and non-purpura nephritis group. Related clinical data were collected from each group; whole blood DNA was extracted from the peripheral blood of subjects, and the iMLDRTM multiplex SNP typing technique was used to determine the genotype of the rs73909842 locus of the DPM1; a statistical analysis was performed. Results There were significant differences in the frequency of C/G, G/G, and C/C genotypes at the rs73909842 locus between the case group and the control group (χ2=7.548,OR=2.593,95%CI=1.292-5.208,P<0.05), and there was also a significant difference in the frequency of C allele between the two groups (χ2=6.053,OR=2.245,95%CI=1.162-4.337,P<0.05). There were no significant diffe-rences in the frequencies of genotypes and alleles at the rs73909842 locus between the above clinical subgroups. Conclusion The single nucleotide polymorphism of the DPM1 gene at the rs73909842 locus was associated with the onset of Henoch-Schönlein purpura in children, and allele C may be a susceptible gene.